Association of acute kidney injury and bleeding events with mortality after radial or femoral access in patients with acute coronary syndrome undergoing invasive management: secondary analysis of a randomized clinical trial. (26th January 2019) - Rothenbühler, Martina; Valgimigli, Marco; Odutayo, Ayodele; Frigoli, Enrico; Leonardi, Sergio; Vranckx, Pascal; Turturo, Maurizio; Moretti, Luciano; Amico, Francesco; Uguccioni, Lucia; Contarini, Marco; Gómez-Hospital, Joan Antoni; et al.
Abstract: Aims: In the Minimizing Adverse Haemorrhagic Events by TRansradial Access Site and Systemic Implementation of angioX (MATRIX) trial, adults with acute coronary syndrome undergoing coronary intervention who were allocated to radial access had a lower risk of bleeding, acute kidney injury (AKI), and all-cause mortality, as compared with those allocated to femoral access. The mechanism of the mortality benefit of radial access remained unclear. Methods and results: We used multistate and competing risk models to determine the effects of radial and femoral access on bleeding, AKI and all-cause mortality in the MATRIX trial and to disentangle the relationship between these different types of events. There were large relative risk reductions in mortality for radial compared with femoral access for the transition from AKI to death [hazard ratio (HR) 0.55, 95% confidence interval (CI) 0.31–0.97] and for the pathway from coronary intervention to AKI to death (HR 0.49, 95% CI 0.26–0.92). Conversely, there was little evidence for a difference between radial and femoral groups for the transition from bleeding to death (HR 1.05, 95% CI 0.42–2.64) and the pathway from coronary intervention to bleeding to death (HR 0.84, 95% CI 0.28–2.49). Conclusion: The prevention of AKI appeared predominantly responsible for the mortality benefit of radial as compared with femoral access in the MATRIX trial. There was little evidence for an equally important, independent role of bleeding.